An introduction of two differential excitation potentials technique in electrical capacitance tomography - Elmy Johana, Mohamad, Dr.; Ruzairi, Abdul Rahim, Prof. Dr.; Leow, Pei Ling, Dr.; Mohd Hafiz Fazalul, Rahiman, Dr.; Omar Mohd Faizan, Marwah; Nor Muzakkir, Nor Ayob; Herlina, Abdul Rahim, Dr.; Fazlul Rahman, Mohd Yunus (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/